Energy Sufficiency of Biomass and Wastewater in Closed Process of Sago Starch Production - Bantacut, Tajuddin; Indriyani, Fitria (Department of Agro-industrial Technology, University of Brawijaya, 2022)
AbstractSago grows in lowland and peat swamp regions that are relatively isolated due to limited basic infrastructures, including energy supply, especially electricity. These limitations constraining the development of sago starch production and industry. The sago starch production process generates by-products such as sago bark waste, pith waste, and wastewater which are potentially used as an energy source. This paper discusses a closed system model of an energy-independent sago starch production process from the utilization of by-products and wastewater. A mass balance model was developed to calculate the energy potency of by-products and waste to construct a closed system for the sago starch production process. The model's output showed that the by-product from processing 1,000 tons of sago stems per day with an optimal yield of 14% potentially generates 90,562 kWh of energy. This energy potency can meet the 26,070 kWh energy needed for sago starch production, making it possible to develop into a closed production system. Further research is needed to determine the site-specific aspects that affect energy sufficiency.Keywords: closed system, energy sufficiency, sago starch AbstrakKawasan hutan sagu berada di dataran rendah dan rawa-rawa yang relatif terisolasi karena keterbatasan infrastruktur dasar, termasuk pasokan energi, terutama listrik. Keterbatasan tersebut menyebabkan produksi dan industri pati sagu sulit berkembang. Proses produksi pati sagu mempunyai hasil samping berupa kulit, ampas, dan limbah cair yang dapat dimanfaatkan sebagai sumber energi. Artikel ini membahas model sistem tertutup proses produksi pati sagu yang mandiri energi dari pemanfaatan hasil samping dan limbah cair. Model kesetimbangan massa dikembangkan untuk menghitung potensi energi dari hasil samping dan limbah untuk membangun sistem tertutup proses produksi pati sagu. Luaran model menunjukkan bahwa hasil samping dari pengolahan 1.000 ton batang sagu per hari dengan rendemen optimal 14% berpotensi membentuk energi sebanyak 90.562 kWh. Potensi energi ini dapat memenuhi kebutuhan energi yang diperlukan dalam pengolahan sebanyak 26.070 kWh, sehingga produksi pati sagu dapat dikembangkan menjadi sistem produksi tertutup. Penelitian lanjutan perlu dilakukan untuk mengetahui aspek spesifik lokasi terhadap kecukupan energi.Kata kunci: kecukupan energi, pati sagu, sistem tertutup